Market oriented extension services to increase food security among farming communities in sri lanka - Perera, K.K.P.; De silva, S. (University of Jaffna, 2012)
High transaction cost, inefficient value chains and lack of capacity to meet market demands for quality, quantity and timeliness have put small farmers in a disadvantaged position in the highly unpredictable market environment in Sri Lanka. Hence, strengthening farming communities through market oriented extension services (MOES) become inevitable. The objective of this paper is to determine the effectiveness of MOES in ensuring food security among farming communities in Sri Lanka. Five cases including 50 farmers of private organizations and/or public-private partnerships, practicing MOES were selected and both quantitative and qualitative data were collected by using a pre tested interview schedule, key informant discussions and observations to achieve the research objective. Innovative MOES activities and performance of agro– enterprises were analyzed. The results revealed that in the conventional agricultural extension system, many producers attempt to produce higher volumes at lower costs (cost leadership) in contrast to MOES where producers attempt to gain competitive advantage through product differentiation (organic and natural products, premium quality , value addition etc.) and niche marketing at local and international markets. Combination of scientific knowledge obtained through better advisory service with traditional indigenous knowledge help the farmers in the MOES system to focus on both production (crop selection, planning, and cultural practices) and marketing (post-harvest handling, quality standards, packing, transportation, hygiene, etc) aspects of their enterprise. Better linkages and coordination of business activities such as production, marketing, distribution and finance, as well as continuous Research and Development (R&D) in respective areas; help the actors in the value chain to increase their profits. The weaknesses of the traditional farmer organizations have been addressed in the new system through forming empowered, networked and profit oriented farmer groups. Innovative and differentiated products with high quality standards; additional benefits or services that justify higher prices ; focus on high –end supermarkets, final processers, and export markets; and promotion through branding and value addition in various advertising media help the farmers to gain profitability , sustainability and equity. In conclusion MOES can provide better solutions to all the actors in agricultural value chain in order to ensure the food security among farming communities.
Keywords: Market orientation; Food security; Value chain